Phase transition behavior in (1 - X)PZT-xBiAlO3 ceramics - N. Tawichai (2018)
In this study, a new ceramic with the composition (1 - x)Pb(Zr0.52Ti0.48)O3-xBiAlO3was fabricated using the solid state method. Phase transition characteristic and dielectric response were investigated. With increase in the content of BiAlO3, a transformation from the tetragonal to the rhombohedral phase was observed. The addition also enhanced the degree of phase transition diffuseness and produced a decrease in the ferroelectric-to-paraelectric phase transition temperature. The results suggested that BiAlO3has a strong effect on the transition behavior of the solid solution. It is proposed that lattice distortion and compositional fluctuation are responsible for these effects. © 2010 Taylor & Francis.